Pengaruh konsep diri dan lingkungan teman sebaya terhadap kemampuan komunikasi interpersonal siswa OTKP SMK Negeri 1 Karanganyar - Liriomyza Kusuma; Tri Murwaningsih; Patni Ninghardjanti (JIKAP (Jurnal Informasi dan Komunikasi Administrasi Perkantoran), 2023)
Abstrak: Studi ini bertujuan untuk menentukan efek dari variabel konsep diri dan lingkungan rekan, sebagian dan secara bersamaan, pada keterampilan komunikasi interpersonal siswa. Penelitian ini adalah kuantitatif dengan metode korelasi. Populasi penelitian ini adalah 216 orang dengan jurusan di kelas OTKP X, XI, dan XII. Penelitian ini menggunakan teknik sampling acak yang proporsional. Penelitian ini mengumpulkan data menggunakan kuesioner dan menggunakan beberapa teknik regresi linear yang didukung oleh IBM SPSS 26 untuk menganalisis data. The results showed that: (1) there was a positive and significant effect of the self- concept variable on students interpersonal communication skills, as evidenced by a significance value of 0,00 0,05 and a t value of 12,227 > Table 1,976; (2) there was a positive and significant effect of the peer environment variable on students interpersonal communication skills, as evidenced by a significance value of 0,000,05 and a t value of 6,272 > Table 1,976; (3) there was a positive and significant effect of the self- concept and peer environment variables on students interpersonal communication skills, as evidenced by a significance value of 0.000.05 and a F value of 203,496>. Ftable 3,063. Hasil penelitian ini menunjukkan bahwa kontribusi efektif secara simultan adalah 67,4% dan bahwa 32,6% yang tersisa dipengaruhi oleh variabel lain yang tidak termasuk dalam penelitian ini.Kata Kunci: correlational method; interpersonal communication; kuantitatifAbstract: This study aims to determine the effect of self-concept and peer environment variables, partially and simultaneously, on students' interpersonal communication skills. This research is quantitative with a correlational method. The population of this research is 216 people majoring in OTKP classes X, XI, and XII. This research used proportionately stratified random sampling techniques. This research collected the data using questionnaires and used multiple linear regression techniques supported by IBM SPSS 26 to analyze the data. The results showed that: (1) there was a positive and significant effect of the self- concept variable on students interpersonal communication skills, as evidenced by a significance value of 0,00 0,05 and a t value of 12,227 > Table 1,976; (2) there was a positive and significant effect of the peer environment variable on students interpersonal communication skills, as evidenced by a significance value of 0,000,05 and a t value of 6,272 > Table 1,976; (3) there was a positive and significant effect of the self-concept and peer environment variables on students interpersonal communication skills, as evidenced by a significance value of 0.000.05 and a F value of 203,496>. Ftable 3,063. The results of this study indicate that the effective contribution is simultaneously 67.4% and that the remaining 32.6% is influenced by other variables not included in this study.Keywords: correlational method; interpersonal communication; quantitative